Plasma levels do not predict thrombin generation in patients taking direct oral anticoagulants. (7th June 2021) - Metze, Michael; Klöter, Tristan; Stöbe, Stephan; Rechenberger, Björn; Siegemund, Roland; Siegemund, Thomas; Laufs, Ulrich; Petros, Sirak; Pfrepper, Christian
Abstract: Background: The antithrombotic effect of direct oral anticoagulants (DOAC) in specific clinical scenarios is difficult to assess. Objective: This study aimed to evaluate the effect of DOAC on thrombin generation (TG) in relation to their plasma level. Methods: Eighty patients newly started on anticoagulation were included, 20 patients for each DOAC—apixaban, edoxaban, rivaroxaban, and dabigatran. Plasma was sampled before DOAC (baseline), at plasma peak time, 6 and 12 hours after starting DOAC for quantification of drug levels and TG. Results: The baseline TG before DOAC intake showed inter‐individual variability. All DOACs significantly prolonged lag time (LT) and time to peak (TTP), but did not change endogenous thrombin potential (ETP). Anti‐Xa inhibitors but not dabigatran reduced thrombin peak, but the effect of apixaban at plasma peak was less pronounced (factor 1.6). LT and TTP prolongation of dabigatran was lower compared to anti‐Xa inhibitors. All DOACs showed a nonlinear dose‐response relationship, with the greatest antithrombotic effect at lower DOAC plasma levels. The inhibition of TG parameters between baseline and peak was parallel between individual patients but the coefficient of variation of TG was lower compared to drug levels. Conclusion: The antithrombotic effect at DOAC peak plasma level measured by TG depends on the patient‐specific baseline TG level and the drug‐specific inhibition by the particular DOAC. Although peak plasma levels have a high variability, the variation of TG is lower compared to drug levels. Therefore, TG assays may be superior to plasma levels in the assessment of the intensity of anticoagulation.